Carbon farming as a future strategy for climate change: A literature review - Pakpahan, Helen Steavy; Masjud, Yunita Ismail (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: This research aims to know about carbon farming and strategies for storing carbon in the soil. Methods: The research method used is qualitative data analysis where this method describes the research conducted by the author by collecting data from scientific journals, books, and research journals. Finding: Respiration plants absorb carbon dioxide and give off oxygen. However, the balance of plants and humans/animals is now disturbed along with the massive and excessive use of fossil fuels. The result is global warming and uncomfortable conditions and health risks to humans and the planet globally. We are currently paying attention to how carbon dioxide is present in the air due to pollution and industrial waste. Various ways are done, including reducing the consumption of petroleum or fossil fuels. Instead of decreasing, the consumption of fossil fuels has not decreased but has increased along with the pace of industrialization in developing countries. Carbon farming is one method that can be a solution, with the principle that problems are solutions. Conclusion: Many strategies for storing carbon in the soil that we already know. As carbon is absorbed by the soil, the health of the soil will improve so that the health of plants will also increase and yields will increase.